ASPEK CITRAAN DALAM NOVEL DIAMDIAM SALING CINTA KARYA ARAFAT NUR - Arina, Sopyan; Sutejo, Sutejo; Astuti, Cutiana Windri (Jurnal Bahasa dan Sastra, 2022)
Literary works serve as a conduit for writers and readers to express their perspectives on variuous issues in human life through the medium of language. Language as a medium for literary works uses imagery as one of the elements of the creation of literary works. This study aimed at describing the use of imagery contained in Arafat Nur’s Novel, Diam-diam Saling Cinta, specifically in the aspects of form and function. This study used descriptive qualitative method. The data collection technique used in this research is the reading and note-taking technique. The steps in data analysis are as follows; (1) data classification, (2) data reduction, (3) data interpretation based on thery, and (4) drawing conclusions. The result of this study found five types of imagery, namely; (1) visual imagery, (2) auditory imagery, (3) motion imagery, (4) tactile imagey,and (5) olfactory imagery. And there are four function of imagery in this novel, namely as a means of describing the characters, describing the setting, building the storyline, and depicting the theme in the novel.